INFLUENCE OF FORMULATION WITH DIFFERENT BINDER MATERIAL TO QUALITY MAKARONI CATFISH (Pangasiushypopthalmus) - Anggi gusdinata; Syahrul Syahrul; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research has been done in BALITBANG Laboratory of white sand, and Laboratory of Fishery Products, Faculty of Fisheries and Marine University of Riau in august 2017. This study aims to determine the effect of adding different flour to the quality of catfish macaroni. The method used in this research is experimental method that is doing macaroni processing with the addition of different flour. The design used was non-factorial Randomized (RAL) design with 4 treatment levels, ie M0: addition of 0g flour, 300g red rice flour, 100g sago flour, M1: 165g flour, 165g red rice flour, 50g sago flour, M2: addition of 180g wheat flour, 150g flour of rice flour sago 50g, M3: addition of wheat flour 300g red rice flour 0g 50g sago flour. The experiment was repeated 3 times, so the number of experimental units in the study was 12 units. Based on organoleptik showed that the most favored treatment of consumer that is M1 organoleptic value from each treatment seen from the value of rupa, taste, aroma, and texture are 7,47,5,7,7,37,83,83. From the results of research that has been done on the treatment of M1 has the color characteristics of dark brown, fish taste is felt, the specific aroma of macaroni, as well as a chewy texture. While the results of proximate analysis seen from moisture content, protein content, fat content, ash content and fiber content. The best are 7.70%, 12.85%, 7.99%, 3.34%, 2.73%. Keywords: Catfish, Macaroni, Red barsa, sago, Wheat flour